Empresas de impacto positivo: um modelo conceitual para criação de valor a partir do design estratégico - Carpenedo, Caroline (Universidade do Vale do Rio dos Sinos, 2021)
The last years have shown how business is changing and the challenges companies face to balance the short-term business results with the need for progress in the long term. In this new context, some companies are reinforcing their purpose to strive for objectives which goes beyond the pure financial results, guaranteeing a positive business impact, and generating value for the whole ecosystem over time. The strategic design can occupy an important space where the businesses can see the value that can be shared among people: customers, suppliers, investors, community, other companies, i.e. the ecosystem and society in general. In addition to being thought-provoking, building the competencies to contribute with the collective change is in the field of strategic design through shared processes as well as to encourage sustainability and social innovation. Therefore, this study aimed to understand how enterprises integrate economic value, sustainability and purpose to generate a positive impact for the entire ecosystem. Thus, a design science research study was carried out with three different companies, having each one the B certification as well as ESG (Environment, social and governance) indicators that are structured and followed by the board of directors. This research achieved its goals by proposing a conceptual model which includes the fundamental elements that companies need to take into consideration to generate positive impact to all ecosystems participants. This thesis contributed to the sustainability, purpose and strategic design field brining examples on how companies who joined the positive impact generation journey are creating, capturing and disseminating value to the whole ecosystem. A second contribution was bringing the benefits that sustainability in the business strategy can bring to organizations. And finally, this study favored the dialogue between the discipline of strategic design and the management area so that we can build a common theoretical framework that brings education, awareness and value creation to the entire ecosystem participants.
Keywords: Design estratégico; Criação de valor; Propósito; Sustentabilidade; ESG; Sistema B; Inovação social; Strategic design; Value creation; Purpose; Sustainability; Business; Social innovation; B System; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial